2019
DOI: 10.1002/pts.2444
|View full text |Cite
|
Sign up to set email alerts
|

Shelf life prediction of oxygen‐sensitive products: The influence of moisture on prediction accuracy for freeze‐dried coffee

Abstract: Optimised packaging requires that properties are matched to the protection requirements of food for its shelf life duration. Benefits include reduced packaging costs, use volumes, and potentially improved environmental performance. The ability to predict product shelf life in different materials can assist in selecting optimal packaging. However, the availability of such tools is limited, and risk for over packing exists. The aim with this work is to develop a prediction approach which can be applied to assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In majority of studies, the authors showed the importance of a well-dimensioned packaging to preserve food and increase shelf life. The strategies proposed were (i) to correctly chose packaging regarding gas and water permeabilities to limit for example the oxidation (Rovira et al, 2019;Witik et al, 2019), or the water intake of dried products (Seth et al, 2018), (ii) use an optimal modified atmosphere to limit for example microbial spoilage (Chaix et al, 2015b;Guillard et al, 2016), quality loss of vegetables (Tsironi et al, 2017) or texture modification (Wyrwisz et al, 2017), and (iii) use an active packaging (ie packaging in which components were deliberately added to be liberated in food or headspace or to absorb a substance to increase the food shelf-life), as antimicrobial compounds (Ag, potassium sorbate etc.) to protect products from microbial growth (Marcuzzo et al, 2013;Apjok et al, 2019).…”
Section: Overview Of Current Modeling Of Shelf Lifementioning
confidence: 99%
“…In majority of studies, the authors showed the importance of a well-dimensioned packaging to preserve food and increase shelf life. The strategies proposed were (i) to correctly chose packaging regarding gas and water permeabilities to limit for example the oxidation (Rovira et al, 2019;Witik et al, 2019), or the water intake of dried products (Seth et al, 2018), (ii) use an optimal modified atmosphere to limit for example microbial spoilage (Chaix et al, 2015b;Guillard et al, 2016), quality loss of vegetables (Tsironi et al, 2017) or texture modification (Wyrwisz et al, 2017), and (iii) use an active packaging (ie packaging in which components were deliberately added to be liberated in food or headspace or to absorb a substance to increase the food shelf-life), as antimicrobial compounds (Ag, potassium sorbate etc.) to protect products from microbial growth (Marcuzzo et al, 2013;Apjok et al, 2019).…”
Section: Overview Of Current Modeling Of Shelf Lifementioning
confidence: 99%
“…This methodology is called Accelerated Shelf-Life Testing (ASLT) and allows us to reduce the time needed to estimate the shelf life of the product (Calligaris et al, 2019). The ability to predict the shelf life of the product in different materials can help select the optimal packaging (Witik et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30] Moisture ingress and permeation evaluation in packaging materials has thus far largely focused on lightweight flexible material. [31][32][33][34] It is inevitable that some amount of moisture permeates through gasket materials, and knowing the rate of diffusion can be useful in predicting a more accurate shelf lives for transported and stored products.…”
Section: Introductionmentioning
confidence: 99%